Validitas perangkat pembelajaran matematika berbasis problem based learning (PBL) dalam upaya memfasilitasi kemampuan penalaran matematika siswa SMA kelas X - Harapit, Syef; Maimunah, Maimunah; Hutapea, Nahor Murani (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This research is motivated by the limited mathematics learning tools as a means of supporting learning in the 2013 Curriculum. The purpose of this research is to produce products in the form of learning tools (syllabus, RPP and LKPD) on the SPLTV material for SMA class X with PBL models that meet valid criteria. Learning tools were developed using the 4D model. The development that the researchers carried out consisted of five stages, namely: (1) define; (2) design; (3) develop; (4) disseminate. The research instrument used was a validity instrument in the form of a validation sheet to assess the feasibility of the syllabus, lesson plans and student worksheet. The results of the validation of the experts stated that the products that succeeded in reaching the very valid category with an average result for the syllabus were 92%, RPP 93% and LKPD 90%.